Letter to Jane Tolmach from May Layne Bonnell - May Layne Bonnell:::::: (1960)
A letter from May Layne Bonnell on behalf of Governor Brown to Jane Tolmach that reccommends B.B. Jenkins for the 31st District Agricultural Association vacancy after the death of Roscoe Burson.